Managing corporate reputation, stakeholder relations, and corporate social responsibility: a Southeast Asian perspective - Abdullah, Zulhamri (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
The purpose of this paper is to identify the importance of and relationships between the three key concepts of corporate reputation, stakeholder relations, and corporate social responsibility from a managerial perspective of corporate communication and corporate marketing. This study employed in-depth interviews with selected companies from GLCs, MNCs, and LPCs. The study found that, despite the significant alignment and integration between corporate reputation, stakeholder relations, and corporate social responsibility in their practice, all these have been managed as business duties (regulated), not genuinely for the substantial contribution to a larger social community and environment (self-regulated). It was also found that, there is discrepancy in practicing CSR between MNCs, GLCs, and LPCs in Malaysia. Although practicing excellent CSR is desirable, in practice, they all are struggling to gain public legitimacy and reputation globally. Findings offer important implication for manager in relation to corporate reputation management.